PEMBERDAYAAN KELOMPOK PKK DESA NGADIRESO MELALUI EDUKASI BAHAYA PERNIKAHAN DINI - Zhuriya Sajida; Hilmi Aldira; Sulistiani Sulistiani; Moch Haikal Maulana Al Farizi; Ali Hamdi; Fitria Vidinia Nur Faizah; Ayu Syarifatul Aulya; Ardelia Salsabila; Akfa Atiatur Rahma; Istichfarin Eka Aul; Nouvena Nur Laila; Humam Afif Al-Mahbubi; Dimas Femy Sasongko (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
Early marriage (EM) is a social phenomenon that happen in various regions in Indonesia, including in Ngadireso Village, Poncokusumo District, Malang Regency. Factors such as pregnancy before marriage, economic pressure, promiscuity, and lack of understanding about the negative impacts of EM are the main causes of the high rate of marriage at a young age. To overcome this problem, empowerment is carried out through socialization as part of the Students’ Community Service (KKM) of UIN Malang. This empowerment aims to increase public awareness, especially parents and teenagers, about the risks and impacts of EM. This activity involves students, village officials, and PKK administrators who play an active role in inviting the society to participate. Through the delivery of material by experts, discussions, and questions and answers, participants are given insight into how to prevent EM and to reduce the rate of EM in the village. The results of the activity show that empowerment through this socialization has received a positive response from the community and is expected to contribute the awareness and readiness for proper marriage. With this activity, it is hoped that efforts to prevent EM can continue to be improved through ongoing education.